Pengaruh Digitalisasi Terhadap Link and Match Mahasiswa dalam Mencari Pekerjaan (Studi Kasus Mahasiswa FEB Universitas Islam Malang Angkatan 2021) - Akmal, Ahmad Mustahiq; Widarko, Agus; Arsyianto, Muhammad Tody (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research examines the effect of digitalization on the alignment between students and job opportunities. Using a quantitative approach, it employs a Likert scale to assess responses from 87 purposively selected participants. Primary data was collected through questionnaires distributed via Google Forms and analyzed using validity and reliability tests, simple regression analysis, hypothesis testing, and the coefficient of determination test in SPSS 26. The results indicate that digitalization plays a significant role in strengthening this alignment, improving the match between students' skills and labor market demands, and enhancing their employment prospects. Keywords: Digitalization, Link and Match, Job Matching.